Konsep Pendidikan Ajaran Tasawuf Sebagai Problem Solving Bagi Kehidupan Spiritual Masyarakat Islam Perkotaan - nisma, nisma (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2025)
There are various factors of the sufism revival in urban society. One of them is the technological establishment which is considered to have failed in overcoming the spiritual crisis of urban communities. So that it becomes a factor causing the multidimensional crisis that characterizes urban society. Currently modern urban society tends to experience what is called alienation (isolation) because its religious rituals are only carried out as a formality without a deep appreciation. Therefore, the revival of the spirit of spiritualism in the midst of urban society engenders new hopes of overcoming the spiritual and moral crisis that has almost disappeared amidst of the rush of science and technology in this modern century.